Developing a scale for emotional intelligence among students in some physical education and sports science colleges in the Kurdistan Region of Iraq, focusing on weightlifting. - Mahmoud, Asst.LShawana Hassan; Rashid, Asst.Prof.Dr.Dunia Najat; Al-Zubaidi, Prof.Dr.Abdulwadood Ahmed (Sulaimani Journal for Humanities, 2026)
This study aims to: 1- Develop an emotional intelligence scale for students in selected physical education and sports science colleges in the Kurdistan Region of Iraq. 2- Identify differences in emotional intelligence among students in selected physical education and sports science colleges in the Kurdistan Region of Iraq. The researchers employed a descriptive survey methodology, deemed suitable for the nature of the research. The study population consisted of students from selected physical education and sports science colleges in the Kurdistan Region of Iraq during the 2024-2025 academic year, totaling 275 students representing three colleges. The research procedures were conducted on this sample, which served as the data collection and application. Statistical methods were used, including the arithmetic mean, standard deviation, percentage, Pearson's correlation coefficient, standard error, and Spearman-Brown rank correlation coefficient. The researchers concluded the following: 1- The emotional intelligence scale, which the researchers developed using established scientific procedures for scale construction, proved effective. 2- The study results showed that the research sample scored higher than the hypothetical average on the emotional intelligence scale. 3- No statistically significant differences were found between the scores of students from different colleges in the Kurdistan Region on the emotional intelligence scale. In light of the findings of this research, the researchers recommend the following: 1- Adopting the emotional intelligence scale developed by the researchers for measurement and evaluation in similar research and studies. 2- Enrolling students in psychological counseling courses and seminars to promote positive attitudes. 3- Conducting further studies on emotional intelligence with other groups participating in different sports.
Keywords: Emotional intelligence; students; physical education and sports science